Incidencia de la inversión pública en el nivel de la actividad económica en el Perú: 1985-2010. - Alvarado Franco, Gilberto Cesar (2011)
In the present investigation it has been evaluated the Public investment and their incidence in the level of economic activity, with the purpose of contributing in the knowledge of the importance that is the public investment for our economy, with an eye toward improving the process of taking of economic politics's makers' decisions. It has been examined the bills of the public sector and of the central government of the registrations statistical quarterly that reports the Central Bank of Reservation of the Peru, such as the average expenses and the expenses in public investment, the statistics were also revised in periods quarterly of the PBI reported by the National Institute of Statistic and Computer, these variables were analyzed through the descriptive statistic. Soon after he/she was considered the following econometric model: PBI = β1 + β2 Public Investment + εt. It was found that during the period of study, the behavior of the public investment has followed a growing tendency, to a rate average 12 annual%, as for the level of the economic activity he/she has also had a growing tendency, mainly in the period 2000 at the 2010, where the rate of growth average is yearly of 6%. In consequence, the good macroeconomic acting has allowed to endow from more resources to the State and at the same time to allow to improve the economic infrastructure, allowing the economic agents to reduce its transaction costs and to enjoy better economic conditions, the levels of competitiveness of the economic activities that are carried out in our country increasing.